Air quality impacts of the 2018 Mt. Kilauea Volcano eruption in Hawaii: A regional chemical transport model study with satellite-constrained emissions. (15th September 2020) - Tang, Youhua; Tong, Daniel Q.; Yang, Kai; Lee, Pius; Baker, Barry; Crawford, Alice; Luke, Winston; Stein, Ariel; Campbell, Patrick C.; Ring, Allison; Flynn, James; Wang, Yuxuan; et al.
Abstract: Volcanic eruptions emit a vast amount of sulfur dioxide (SO2 ) and ash into the air, often imposing substantial impacts on air quality and the ecosystem. Quantifying its impacts, however, is difficult due to the uncertainties in estimating the strength and variations of volcanic emissions. Here we developed and evaluated a new approach to combine satellite SO2 detection and chemical transport modeling to assess the impact of the 2018 Mt. Kilauea eruption on air quality over Hawaii. During the sustained eruption of the Kilauea Volcano in Hawaii's Big Island from May to July 2018, considerable SO2 and PM2.5 enhancements were observed both from the ground and from space. We studied this case using an experimental version of the NOAA National Air Quality Forecast Capability (NAQFC) modeling system. Daily emissions of SO2 and ash were estimated using a combination of SO2 column density retrieved by Ozone Mapping and Profiling Suite (OMPS) Nadir-Mapper (NM) aboard the Suomi-NPP satellite and the NAQFC model with an inverse emission modeling approach. We found that the volcanic SO2 emission rates peaked at 15, 000 mol/s from the Kilauea's East Rift zone and Summit. The formation and transport of volcanic smog, or Vog, was highly dependent upon the vertical distribution of the volcanic emission, controlled by the heat flux of emission sources. We conducted four model simulations with various emission settings, and compared them to satellite data (CALIOP, OMPS and VIIRS) and in-situ measurements. All the runs tended to underpredict the peak values of surface SO2 and PM2.5 (particulate matter smaller than 2.5 μm in diameter). The "No Plume Rise" run underestimated the Vog plume rise and downstream transport. Using fixed emission rate or removing the temporal variations ("3-Day Mean") led to miss peak Vog effects or inconsistent transport pattern compared to the observations. Therefore, the Base simulation with daily-varying emission and plume rise was used to quantify the air quality effects of the Kilauea eruption. We found that the volcanic eruption elevated surface PM2.5 concentration by 30–40 μg/m 3 in the southeast part of the Big Island, with peak values up to 300 μg/m 3 . The Vog effect on trace gases, such as O3, NOx, and non-methane hydrocarbons, were much weaker (<1 ppbV), but extended to farther downstream. Highlights: The Kilauea volcano had major eruption in May–July 2018. Satellite SO2 retrievals are used to estimate volcanic emission for model studies. The plume rise of volcanic smog highly depends on the lava heat flux. Satellite and in-situ measurement data are used to verify the four model runs. Regional SO2 and particle matters are the major volcanic influences.